Vibration Control and Structure Integration of antennas on aircraft - Research in NATO SET-131 - Knott, P.; Loecker, C.; Algermissen, S.; Sekora, R. (2013 7th European Conference on Antennas and Propagation, 2013)
Conformal and structure integrated antennas mounted on aircraft will play an increasingly important role in future wireless systems. Such antennas have advantages against conventional antenna design but are subject to vibrations and deformations caused e.g. by aerodynamic loads, vehicle motion or moving parts such as the turbine or jet engine. Effects of vibrations and deformations on the performance of radar, navigation or communication systems are in the scope of the NATO research task group SET-131 "Vibration Control and Structure Integration of Antennas". The paper describes research activities within the group and gives an update of a demonstrator system comprising a conformal seven element antenna array with active vibration control.